The Legal Regulation Model of Open Banking in China (Global Journal of Human-Social Science, 2023)
Although open banking has been developed rapidly in China since 2018 there is not a clear legal regulatory framework Open banking can stimulate competition provide better services to customers and reduce the traditional screen-scrapping risk However it causes concerns over data security customer privacy data abuse and challenges to current Chinese regulatory system Therefore it is necessary to establish a better regulatory system for open banking in China Through learning from regulation forms in other jurisdiction it is found that active guidance regulation is more appropriate for China which requires government to provide standards for open banking but not force banks to share data Under the Active Guidance model it is necessary to improve current Chinese regulatory and legal regime including establishing feasible rules for data portability implementation constructing a multi-level regulatory system for data sharing as well as changing data privacy protection mode from Notice- Consent to Data Autonomy
Keywords: open banking; data sharing; data autonomy; data privacy; data portability